Maternal plasma urocortin level as a biomarker of preterm birth: a prospective cohort study in Sulaimaniyah city in Iraq - Sallama Kamel Nasir (Journal of International Medical Research)
Objective To evaluate the value of the urocortin (UCN) level to predict preterm delivery in women with threatened preterm labour. Methods This prospective cohort study included 96 women with a singleton pregnancy between 28 and 34 weeks of gestation who were admitted with threatened preterm labour. The participants were monitored until delivery. The UCN level was compared between those with preterm and with full-term deliveries. Results The mean UCN level was higher for preterm deliveries (96 ± 24.34 pg/mL) than for full-term deliveries (62.62 ± 23.63 pg/mL). A UCN cutoff level of 92 pg/mL had 20% sensitivity, 100% specificity, 100% positive predictive value, and 10% negative predictive value. Thus, 17.7% of women had a UCN level ≥ 92 pg/mL, and all delivered preterm. Among the 82.3% of women who had a UCN level < 92 pg/mL, 88.6% delivered preterm, and 11.4% delivered at full term. Moreover, 88.2% of women who had a UCN level ≥ 92 pg/mL delivered within 7 days and only 11.8% delivered after 7 days. However, 58.2% of women with a UCN level < 92 pg/mL delivered within 7 days and 41.8% delivered after 7 days. Conclusion A UCN cutoff level of ≥92 pg/mL predicts preterm delivery within 7 days of admission.